Marta López Gil, Filosofía, modernidad y posmodernidad, Buenos Aires, Biblos, 1996, 220 páginas. - Barbuto, Marcelo Alberto (1996)
Fil: Barbuto, Marcelo Alberto. Universidad de Buenos Aires; Argentina.